2006
DOI: 10.1128/mcb.01991-05
|View full text |Cite
|
Sign up to set email alerts
|

Human Transcription Elongation Factor CA150 Localizes to Splicing Factor-Rich Nuclear Speckles and Assembles Transcription and Splicing Components into Complexes through Its Amino and Carboxyl Regions

Abstract: , respectively. WW and FF domains may, therefore, serve to link transcription and splicing components and play a role in coupling transcription and splicing in vivo. In the study presented here, we investigated the subcellular localization and association of CA150 with factors involved in pre-mRNA transcriptional elongation and splicing. Endogenous CA150 colocalized with nuclear speckles, and this was not affected either by inhibition of cellular transcription or by RNAPII CTD phosphorylation. FF domains are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 78 publications
5
77
0
Order By: Relevance
“…In addition, Prp40, the yeast ortholog of FBP11, binds the branch-point bridging protein, U5 small nuclear ribonucleoprotein-associated protein (29,30), U1 small nuclear ribonucleoprotein, and C-terminal domain of RNA polymerase II of RNA polymerase II (31,32). RNA polymerase II is the main coordinator for pre-mRNA processing events, and CA150, another homologue of FBP11, assembles the splicing complex (33). Recent study has shown that MeCP2 regulates excitatory neurotransmission by repressing transcription (34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Prp40, the yeast ortholog of FBP11, binds the branch-point bridging protein, U5 small nuclear ribonucleoprotein-associated protein (29,30), U1 small nuclear ribonucleoprotein, and C-terminal domain of RNA polymerase II of RNA polymerase II (31,32). RNA polymerase II is the main coordinator for pre-mRNA processing events, and CA150, another homologue of FBP11, assembles the splicing complex (33). Recent study has shown that MeCP2 regulates excitatory neurotransmission by repressing transcription (34).…”
Section: Discussionmentioning
confidence: 99%
“…The DRE element was assessed in each orientation by cloning the sequence into KpnI/BglII sites of pGL3 control or pGL3 basic (Promega). Expression vectors encoding TCERG1 were described previously (16). pCMV-FOXM1 expression vector and FOXA luciferase reporter vector were provided by Dr. R. Costa (17).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the transcriptional elongation factor CA150 is able to bridge the splicing factor SF1 via its WW domain and phosphorylated CTD through its FF domain [35,36]; and interestingly, the interaction between CA150 and several splicing factors seems to subject to regulation by arginine methylation [37]. The transcriptional elongation factor TAT-SF1 forms a stable complex with the spliceosome [38] and its homologue in yeast (Cus2) has been shown to function as a critical proofreading enzyme during early spliceosome assembly [39,40], suggesting that TAT-SF1/Cus2 may be a dual function protein in transcription and mRNA splicing.…”
Section: Multiple Molecular Contacts To Facilitate Functional Couplingmentioning
confidence: 99%